Aplicação do laser de baixa intensidade no processo de cicatrização de ferida cirúrgica: padronização dos parâmetros dosimétricos - Aline Gomes Afonso Ferreira (2016)
Damage caused by increased length of hospital stay due to delayed wound healing or infection of surgical wounds have been issues of concern in different contexts of health practices. Early intervention in the treatment of surgical wound through the low-intensity laser application can be an important therapeutic strategy in accelerating the healing, infection prophylaxis, reducing complications and significant reduction in spending on health care services. The lack of standardization of laser irradiation parameters and the wide variety of experimental methods limit the comparison of results between studies and replication of benefits in clinical practice. This study aimed to evaluate the effectiveness of low level laser therapy on wound healing and to investigate the importance of dosimetric parameters in the development of experimental and clinical studies. A survey regarding low intensity laser on the repair of the surgical wound and modulation parameters was performed in Medline, Pubmed, Scielo and Science Direct. Articles were selected from January 2005 to July 2015. A total of 416 articles were found and 27 included, 181 duplicate studies and 201 studies did not meet the inclusion criteria and were therefore excluded. All information related to the dosimetric parameters provided by the studies were grouped in a table that allow for identification of possible flaws in the specification details on irradiation parameters. Calculation for conference of dosimetric parameters were performed in all analyzed articles. This study demostrated that low intensity laser in bands of red wavelength and Infrared is an effective therapy in the repair of the surgical wound. However, we observed great divergence and lack of detailed information on the dosimetric parameters. In this study, it proposed a medical record based on all dosimetric parameters essential to the accurate reproduction of the research in order to standardize the conduct and guide researchers and health professionals regarding the correct application of the laser. It can be concluded that the low-intensity laser is effective in healing the wound by photobiomodulation process. The studies analyzed did not report enough dosimetric parameters for the standardization of applications. It is expected that the proposed medical records will guide researchers and health professionals in the standardization of applications of laser therapy.